Evaluation of nitrogen uptake efficiency of different oil palm genotypes using 15N isotope labelling method - Law, C. C.; Abdul Rahman, Zaharah; Mohd Hanif, Ahmad Husni; Abdullah, Siti Nor Akmar (Universiti Putra Malaysia Press, 2012)
High demands for palm oil world wide induce the expansion of oil palm plantations in Malaysia. Malaysian soils which are highly weathered require high nitrogen fertilizer input in order to maintain high yield output, resulting in increase in production cost as well as inducing negative impacts to the environment. It is crucial to understand the performance of different oil palm genotypes in taking up nitrogen to increase nitrogen use efficiency, minimize environmental pollution caused by leached nitrate and maximize plantation profit, while maintaining sustainable agriculture practices. 15N labelling method was utilized in a greenhouse study to quantify the nitrogen up-take performance of nine oil palm genotypes at 6 and 9 months after planting. Measurements of total dry matter, total N, and percentage N derived from fertilizer (%NdFF) were carried out during the study. At 6 month old, oil palms of different genotypes did not show any difference in nitrogen uptake with and without P fertilizer applications. However, 9 months old oil palms demonstrated significant differences between the genotypes in total dry matter production and total N taken up, hence, resulting in significant differences in N derived from fertilizer among genotypes. Oil palms at 9 months old also showed significant effects in the N uptake as affected by P fertilizer application. Genotype A (14/34 x 2367/17) demonstrated significantly higher nitrogen uptake compared to other genotypes, except for genotype F (9/103 x 2318/17). Thus, the 15N labelling technique could serve as a useful assessment to the nitrogen uptake abilities of oil palm genotypes.